“Subjetivicing the objectivity”. On purpose of the determination of customs infringements - Guadalupe Báscones, Julio (2015)
This article addresses the issue referred to the sanctioning power of the State, which is exercised in two areas (penal and administrative) derived from a single power that allows the State to repress behaviors considered harmful to the development of society. Likewise, the authors have analyzed the Administrative General Procedure Law, where it has been clearly established that all sanctioning administrative procedure should apply the basic principles that protect the rights of the citizens. In this way, the State must apply the principle of guilt, principles of causation, presumption of innocence, among others, to judge customs infringements.